066 Contactin-1-mediated chronic inflammatory demyelinating polyneuropathy (CIDP) presenting as an acute case of guillain bare syndrome (GBS). (23rd August 2021) - Cameron, Shane; Haddad, Rami
Abstract : New and emerging evidence describing the role of autoantibodies to nodal and paranodal proteins in the pathogenesis of chronic inflammatory demyelinating polyneuropathy (CIDP) has arisen over the past decade, with significant diagnostic, therapeutic and prognostic implications. Although rare, CIDP with anti-contactin-1 (CNTN1) IgG4 antibodies has a distinct pathogenesis and clinical phenotype that differs from both typical CIDP and its other atypical variants. Here, we report the case of a young normally well 49-year-old man from rural Australia with severe refractory anti-CNTN1-mediated CIPD who presented like a case of Guillain-Barré syndrome (GBS) who improved dramatically after chemoimmunotherapy with Rituximab and who also had an unexpected late response to subsequent treatments with intravenous immunoglobulin (IVIg). In reporting this case, we hope to highlight important considerations in the diagnosis and treatment of patients with severe refractory CIDP, and especially those patients with anti-CNTN1 seropositive disease. References: Vural A, Doppler K, Meini E. Autoantibodies against the node of ranvier in seropositive chronic inflammatory demyelinating polyneuropathy: diagnostic, pathogenic, and therapeutic relevance. Frontiers in Immunology 2018;9 :1–14. Miura Y, Devaux JJ, Fukami Y, Manso C, Belghazi M, Wong AHY, et al . Contactin 1 IgG4 associates to chronic inflammatory demyelinating polyneuropathy with sensory ataxia. Brain 2015;138 :1484–1491. Bunschoten C, et al . Progress in diagnosis and treatment of chronic inflammatory demyelinating polyradiculoneuropathy. The Lancet Neurology 2019;18(8):784–794. Querol L, Nogales-Gadea G, Rojas-Garcia R, et al . Antibodies to contactin-1 in chronic inflammatory demyelinating polyneuropathy. Annals of Neurology 2013;73 :370–380. Querol L, et al . Rituximab in treatment-resistant CIDP with antibodies against paranodal proteins. Neurology, Neuroimmunology & Neuroinflammation 2015;2(5):1–6.